2010
DOI: 10.1177/0956797610394661
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Sensitive Period for Acculturation

Abstract: Though recent adult immigrants often seem less acculturated to their new society than people who immigrated as children, it is not clear whether this difference is driven by duration of exposure or exposure during a sensitive developmental period. In a study aimed at disambiguating these influences, community and student samples of Hong Kong immigrants to Vancouver, Canada, completed the Vancouver Index of Acculturation, a measure that assesses respondents' identification with their mainstream and heritage cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(82 citation statements)
references
References 25 publications
10
66
2
4
Order By: Relevance
“…Moreover, the reasons behind parentification behavior among immigrant adolescents and the consequences of it were also still a matter of much debate. One possible explanation was the faster socio-cultural adaptation of adolescents as compared to adults (Cheung et al 2011). The research presented here was conducted to shed some light on these topics by investigating emotional and instrumental parentification among mother-adolescent dyads from the former Soviet Union and among a native German comparison group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the reasons behind parentification behavior among immigrant adolescents and the consequences of it were also still a matter of much debate. One possible explanation was the faster socio-cultural adaptation of adolescents as compared to adults (Cheung et al 2011). The research presented here was conducted to shed some light on these topics by investigating emotional and instrumental parentification among mother-adolescent dyads from the former Soviet Union and among a native German comparison group.…”
Section: Discussionmentioning
confidence: 97%
“…For immigrant parents, the reasons for this incapacitation may be that they lack the socio-cultural skills for dealing with acculturation-related demands. Their children, however, have more contact to the new society, adjust faster, and often outperform their parents in sociocultural skills related to the new cultural context (Birman and Trickett 2001;Cheung et al 2011;Telzer 2011), thereby creating an acculturation gap between parents and their children (Birman 2006;Telzer 2011). The different pace in acculturation between parents and adolescents seems to be common and has been found in various ethnic groups and various dimensions of socio-cultural adaptation (Birman 2006;Telzer 2011) as well as among ethnic German immigrant families (Nauck 2001;Schmitt-Rodermund and Silbereisen 2009).…”
Section: Parentification In Immigrant Familiesmentioning
confidence: 93%
“…For immigrants, however, additional parent-child dynamics have to be considered. We have already indicated that immigrant adolescents seem to adjust to a new context more quickly (Cheung et al 2011), which results in an acculturation gap (Birman 2006;Telzer 2011) and in adolescents' taking over responsibilities. These responsibilities are often related to language brokering activities (Morales and Hanson 2005;Weisskirch 2005), which means that adolescents translate documents, bills, and so forth for their parents (Weisskirch 2005), a behavior that is exhibited by approximately 90% of immigrant adolescents, but with substantial interindividual variation (Jones and Trickett 2005;Morales and Hanson 2005).…”
Section: Interdyadic Differences In Mother-adolescent Agreementmentioning
confidence: 96%
“…Whereas immigrant mothers may have the feeling that their children do tell them what happens in school, the adolescents may be hesitant about doing so because their behavior at school, for example, may not conform completely to the mothers' values. A second argument relates to additional differences between mothers and adolescents due to different paces of adaptation (Cheung et al 2011). Usually, adolescents adapt more rapidly than their parents to a new cultural environment, which results in an acculturative gap (Birman 2006;Telzer 2011) and in children taking over family responsibilities, such as translating documents for their parents (language brokering) (Morales and Hanson 2005;Weisskirch 2005), or assuming adult roles (parentification) (Titzmann 2012).…”
Section: Ethnic Group Differences In Mother-adolescent Agreementmentioning
confidence: 99%
See 1 more Smart Citation